Feasibility of Solution-Focused Brief Therapy for Individuals with Alcohol Use in Primary Health Care - Barria-Ramirez, R (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Chile presents one of the highest rates of alcohol use in the continent. A feasibility pre-post-study was conducted to evaluate alcohol use patterns and other mental health issues in 14 patients with hazardous alcohol use, after 3.6 Solution-focused Brief Therapy sessions in primary care. Non-parametric inferential statistical analyses were conducted. Statistically significant decreases and large effect sizes were found in patterns of alcohol use, consequences of alcohol use, and depressive symptoms. Results build on prior literature. Implications for practice, policy, and research related to culturally sensitive brief interventions implemented by social workers in Chile are discussed.
Keywords: Alcoholism; primary health care; Solution-focused Brief Therapy